Antibacterial active open-porous hydroxyapatite/lysozyme scaffolds suitable as bone graft and depot for localised drug delivery. (March 2017) - Mueller, Berit; Treccani, Laura; Rezwan, Kurosch
An engineered synthetic scaffold for bone regeneration should provide temporary structural support and a medium for controlled and localised release of bioavailable medical drugs. In this work, a method is proposed to incorporate biologically active agents without impairing agent activity into open-porous resorbable hydroxyapatite scaffolds. Scaffolds are obtained by a one-pot freeze gelation process and loaded with different amounts of lysozyme, a model macromolecular drug with antibacterial activity. The antibacterial activity is tested by submerging hydroxyapatite scaffolds with 0.5 to 2.5 wt.% lysozyme into two different bacteria stock solutions. A complete dieback of M . luteus bacteria when in contact with the scaffolds is observed. Higher lysozyme amount in the scaffold leads to faster dieback. In contact with scaffolds containing 2.5 wt.% lysozyme after 30 min, no viable bacteria can be observed. An amount of 0.5 wt.% lysozyme in the scaffolds is sufficient to kill all bacteria after a contact time of 24 h. For L. innocua, a bacteriostatic effect is observed. The scaffolds have spongiosa -like stability and are suitable bone implant substitutes. As agents are released from the scaffolds by degrees over a time period of at least 9 days, they are particularly attractive as depot for localised drug delivery of bioactive macromolecular drugs.